Influence of variety (hybrid) on the productivity and biochemical indexes of vegetable marrow in the conditions of south part of western Forest-Steppe of Ukraine - Гойсюк, Л. В. (Scientific Progress & Innovations, 2012)
The problem of biochemical composition of vegetable marrow variety of Chaklun and hybrids of Mostra F1 and Sungroom F1 is considered, sowing of which was conducted in the first ten-day period of May after according to the chart of placing plants 70x70 sm. The content of dry matter, sugar, vitamin C and nitrates is analysed in the fruit of vegetable marrow. The analysis of the productivity of variety and hybrids of vegetable marrow in the conditions of south part of western Forest-Steppe of Ukraine is also given. It has been established that the hybrid of vegetable marrow Sungroom F1 was the most productive (87,65 t/ha) as a result of researches.